Positional Therapy and Regional Pulmonary Ventilation: High-resolution Alignment of Prone and Supine Computed Tomography Images in a Large Animal Model. (November 2020) - Xin, Yi; Cereda, Maurizio; Hamedani, Hooman; Martin, Kevin T.; Tustison, Nicholas J.; Pourfathi, Mehrdad; Kadlecek, Stephen; Siddiqui, Sarmad; Amzajerdian, Faraz; Connell, Marc; Abate, Nicholas; Kajanaku, Agi; et al.
Abstract : Background: Prone ventilation redistributes lung inflation along the gravitational axis; however, localized, nongravitational effects of body position are less well characterized. The authors hypothesize that positional inflation improvements follow both gravitational and nongravitational distributions. This study is a nonoverlapping reanalysis of previously published large animal data. Methods: Five intubated, mechanically ventilated pigs were imaged before and after lung injury by tracheal injection of hydrochloric acid (2 ml/kg). Computed tomography scans were performed at 5 and 10 cm H2 O positive end-expiratory pressure (PEEP) in both prone and supine positions. All paired prone–supine images were digitally aligned to each other. Each unit of lung tissue was assigned to three clusters (K-means) according to positional changes of its density and dimensions. The regional cluster distribution was analyzed. Units of tissue displaying lung recruitment were mapped. Results: We characterized three tissue clusters on computed tomography: deflation (increased tissue density and contraction), limited response (stable density and volume), and reinflation (decreased density and expansion). The respective clusters occupied (mean ± SD including all studied conditions) 29.3 ± 12.9%, 47.6 ± 11.4%, and 23.1 ± 8.3% of total lung mass, with similar distributions before and after lung injury. Reinflation was slightly greater at higher PEEP after injury. Larger proportions of the reinflation cluster were contained in the dorsal versus ventral (86.4 ± 8.5% vs . 13.6 ± 8.5%, P < 0.001) and in the caudal versus cranial (63.4 ± 11.2% vs . 36.6 ± 11.2%, P < 0.001) regions of the lung. After injury, prone positioning recruited 64.5 ± 36.7 g of tissue (11.4 ± 6.7% of total lung mass) at lower PEEP, and 49.9 ± 12.9 g (8.9 ± 2.8% of total mass) at higher PEEP; more than 59.0% of this recruitment was caudal. Conclusions: During mechanical ventilation, lung reinflation and recruitment by the prone positioning were primarily localized in the dorso-caudal lung. The local effects of positioning in this lung region may determine its clinical efficacy. Abstract : The authors utilized their previously reported computed tomography data from five mechanically ventilated sedated pigs before and after lung injury by tracheal administration of hydrocholoric acid to assess positional inflation characteristics in response to supine and prone positioning and two levels of positive end-expiratory pressure (5 and 10 cm H2 O) applied in random order. Regional cluster distributions of units of paired, digitally aligned prone and supine lung tissue according to density and deformation dimensions (deflation, stable density/volume, and reinflation) were analyzed. Patterns followed both gravitational and nongravitational distributions. Reinflation was concentrated in the caudal lung region near the dorsal portion of the diaphragm. Recruitment of nonaerated tissue contributed to reinflation in this region after injury. The demonstrated clinical benefits of prone positioning may be related to localized changes (recruitment or reinflation) in the dorso–caudal lung region, a hypothesis that awaits further testing.Supplemental Digital Content is available in the text.